Women’s Empowerment Through Training in Cloth Pad Production: Implications for Reproductive Health and Economic Independence - Anggi Yus Susilowati (UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines the impact of women's empowerment through training in making cloth sanitary napkins in Kesenden Village. The main issues raised are women's limited access to hygienic and affordable menstrual products, as well as the lack of economic opportunities for housewives. The purpose of the study was to analyze the impact of the training on the reproductive health and economic independence of participants in Kesenden Village. This study used a descriptive qualitative approach. Informants were selected purposively from PKK members who participated in the training. Data were collected through in-depth interviews and participant observations, then analyzed thematically. The results showed that the training had a significant positive impact. From the reproductive health aspect, there was an increase in knowledge and practices of menstrual hygiene among participants, which has the potential to reduce the risk of infection. From the economic independence aspect, this training not only resulted in savings in routine household expenses thanks to independent cloth sanitary napkin production, but also opened up new entrepreneurial opportunities that allowed participants to earn additional income. In conclusion, the cloth sanitary napkin training program in Kesenden Village was effective in empowering women holistically. This initiative not only improved the quality of reproductive health, but also strengthened economic independence, which ultimately contributed to improving the welfare of families and the community as a whole.